Phylogenetic assessment of ultrastructural and histological characters of teeth in the Anostomoidea, Hemiodontidae and Parodontidae (Teleostei: Ostariophysi: Characiformes) - Scharcansky, Alexandre; Lucena, Carlos Alberto S. (Zootaxa, 2008)
The ultrastructure and histology of teeth of members of the order Characiformes, in conjunction with the examination of cleared and stained sections and teeth, revealed characters pertinent to understanding the relationships among the Anostomoidea (Curimatidae, Prochilodontidae, Anostomidae, and Chilodontidae), Hemiodontidae, and Parodontidae. The superimposition of these characters onto cladograms of Characiform phylogeny based on morphological and molecular characters confirmed the monophyly of the Anostomoidea, but resulted in conflicting interpretations concerning the relationships of the Hemiodontidae and Parodontidae.